Connections between Tatars in Petrograd-Leningrad and Finland during the 1920s and 1930s - Bekkin, Renat (Studia Orientalia Electronica, 2020)
Saint Petersburg served from the end of the nineteenth century as a transit point for Mishär Tatars moving to the Grand Duchy of Finland. At the beginning of the twentieth century, a small community had already formed in Finland, but its members maintained regular contacts with their relatives and connections in the Sergach district (Nizhny Novgorod province), Saint Petersburg and other regions. Contrary to common belief, these ties were not interrupted even after the October Revolution of 1917. Throughout most of the 1920s, Tatars and others crossed the Soviet-Finnish border illegally. Tatars living in independent Finland also sent considerable financial aid to their contacts in Leningrad with the help of couriers. The nature of the ties between the Tatar emigrants in Finland and the Tatars of Leningrad can be illustrated by the materials of one criminal case. This case was instituted by the Soviet political police against representatives of the Tatar Muslim community in Leningrad in 1931. Only after several arrests and tightening border control was communication between the Tatars in Finland and Leningrad interrupted. I suggest that the Mishär Tatars in Leningrad and Finland constituted a single social and cultural space until the 1930s, when the connections between them were blocked. The ensuing divide had a large impact on the identity of the Tatars living in Finland, who began developing a separate Finnish Tatar identity just a few years after the termination of contacts.